Konsep Historis Al-Qur’an dalam Pandangan John Wansbrough: Sebuah Tinjauan worldview Islam - Muslih, M Kholid; Muttaqin, Muhamad Shofwan; Sahidin, Amir (Institut Agama Islam Negeri (IAIN) Curup, 2023)
In the book of Qur'anic Studies: Sources and Methods of Scriptural Interpretation, John Wansbrough gives a very sharp critique of the Qur'an. He argues, the Qur'an originates from the Judeo-Christian tradition and the intervention of the Prophet Muhammad on the contents of the Qur'an. Furthermore, it is understood in the view of the life of Muslims that the Qur'an is a holy book sourced from God without any human intervention. For this reason, This paper aims to provide a critical note on John Wansbrough's thoughts on the Qur'an with an overview of the Islamic worldview. This study is a literature study, tracing the works of John Wansbrough both from primary and secondary sources. The results of this study show the evidence: first of all, John Wansbrough's thought is not appropriate for studying and criticizing Qur'an, because he used the methods of historical criticism and literary criticism. Second, both methods have the same result, namely the questionable authenticity of the Qur'an, as in Jewish and Christian scriptures. Third, Wansbrough's fallacy is based on a wrong perspective on key concepts in Islam, i.e, the concepts of God, Prophethood, and Revelation in Islam.